Hybrid spaces: Melbourne Museum's Jurassic World: The Exhibition. Issue 1 (1st March 2018) - Balanzategui, Jessica; Ndalianis, Angela
In 2016, The Melbourne Museum staged the world premiere of Jurassic World: The Exhibition, a globally touring exhibition inspired by Universal Pictures' blockbuster film, Jurassic World (2015), featuring animatronic dinosaurs created by Melbourne's Creature Technology. The exhibition had the most successful opening month of any exhibition at the Museum to date, selling over 100, 000 tickets. Yet Jurassic World also met with controversy for its theme park-esque design and pervasive branding, prioritization of spectacle and attraction over cultural heritage and education, and seamless integration of fact and fiction. In this article, we carry out a close analysis of Jurassic World's combination of theme park and museum exhibition practices, situating the exhibition as a particularly significant example of the developing trend towards the creation of immersive 'narrative environments' in twenty-first century museums, as museums increasingly draw upon the devices of popular entertainment to engage and attract guests. Drawing from Norman Klein's model of the 'scripted space' and Joseph Pine and James Gilmore's 'experience economy', which has its roots in Disney theme parks, our analysis shows how Jurassic World plays with the boundaries of fact and fiction in a way that self-reflexively interrogates the contemporary relationship between popular entertainment and museums.